Climate-Smart Agriculture in Belize: Identifying Investment Priorities - International Center for Tropical Agriculture; World Bank (2018)
This document presents a multi-criteria framework for identifying and prioritizing CSA practices and technologies for Belize. A multi-phase participatory exercise using the CSA-Prioritization Framework can help policymakers target scarce CSA investment resources more effectively.